O "ofício de aluno" e o "ofício de criança": articulações entre a sociologia da educação e a sociologia da infância - Rita de Cássia Marchi (Universidade do Minho, 2010)
This article establishes the relationships between what is known as the "paradigm crisis" in the Sociology of Education (SED) in the 90's and the appearance of a new paradigm for the social studies of childhood. As the central elements of this new paradigm we have the principles of childhood social construction and of child-actor and the requirement of the conceptual autonomy of childhood. The initial separation between the Sociology of Education and the social studies of childwood was due to the fact the SED has been traditionally focused, both on its structural-functional side and on the reproduction theories space as well, on the macro-relationships between school and society. The "child task" and the "student task" have here a complex existence whose clarification reveals the paths which have been exploited in the theoretical-methodological constructions inside these disciplines and in their tense articulations.